Penyuluhan Tentang Risiko Anemia Pada Remaja di Desa Pandanwangi Kecamatan Diwek Kabupaten Jombang - Faris Hamidi; Awaluddin Susanto; Dina Novita Kartika Sari (Yayasan Daarul Huda Kruengmane, 2023)
Adolescent girls are more susceptible to anemia because adolescents are in a growth period that requires higher levels of nutrients, including iron. The prevalence of anemia among children aged 5-12 in Indonesia is 26%, in women aged 13-18, it is 23%. In Riau Province, the prevalence of anemia is 25.1% and 19.4% are at the age of 15-24 years. The impact of anemia on young women is stunted growth, easy infection, resulting in reduced fitness or body fitness, decreased enthusiasm for learning or achievement. As for the results of examinations at the youth posyandu in Pandanwangi Village, the results of the Hb values in adolescents were still in the normal range.